Research progress and application prospect of hydrogen storage technology in underground space - Mincong WANG; Lei HOU; Xueting WANG; Muqingyun YANG; Zicong XU; Yueqi LIU; Shuyan ZHU (You-qi chuyun, 2025)
ObjectiveWith the ongoing advancements in the “carbon peaking and carbon neutrality” strategy and sustainable development goals, hydrogen energy, as a secondary energy source, has garnered significant attention both in China and internationally, due to its abundant availability, eco-friendliness, and low carbon emissions, along with its wide-ranging applications. Underground hydrogen storage has emerged as an effective method for achieving large-scale and long-term storage of hydrogen energy. In comparison to other countries, China relatively falls behind in its research and development of underground hydrogen storage and currently lacks completed engineering cases of such systems. MethodsThis paper presents investigations into the technology of hydrogen storage in underground spaces, focusing on the advantages and disadvantages of four types of geological bodies used for hydrogen storage: salt caverns, depleted oil and gas reservoirs, aquifers, and lined caverns, along with their respective storage characteristics. The discussion further examines the key challenges and potential risks associated with underground hydrogen storage, particularly in the context of depleted oil and gas reservoirs and salt caverns, based on typical cases from abroad. A systematic analysis of the risks encountered in this field is provided, specifically addressing geological body integrity, wellbore integrity, geochemical reactions, and microbial interactions. The impacts of these various risks on the two selected types of hydrogen storage are compared. Moreover, the paper explores adaptation models for underground hydrogen storage across three application scenarios: electricity-hydrogen, electricity-hydrogen-electricity, and electricity-hydrogen-methane. This analysis considers the diversity of hydrogen application scenarios and the characteristics of underground hydrogen storage, such as large capacities, long durations, and geological constraints, with the aim of broadening application scenarios and promoting the coordinated development of the hydrogen energy sector. Furthermore, the potential for future development of these three application models is discussed. ResultsHydrogen storage in depleted oil and gas reservoirs and salt caverns encounters various risks and challenges during actual operation. However, compared to depleted oil and gas reservoirs, salt caverns pose a lower risk of hydrogen leakage through the surrounding rock and result in smaller hydrogen losses due to geochemical and microbial reactions. The underground hydrogen storage technology shows potential for adaptive development across the three hydrogen application scenarios examined. Nevertheless, the two models—electricity-hydrogen-electricity and electricity-hydrogen-methane—currently face bottlenecks, such as low energy conversion efficiencies and high economic costs. ConclusionThe technology of hydrogen storage in underground spaces holds significant market potential for the large-scale application of hydrogen energy in the future. Considering foreign experience of underground hydrogen storage and the identified risks and challenges, salt caverns can be regarded as the most mature and optimal option for underground hydrogen storage available today. Priority should be given to developing the “electricity-hydrogen” coordinated model, with hydrogen as the terminal application, to establish green, efficient, and cost-effective low-carbon energy systems.